TRANSFORMING TEACHING AND LEARNING PARADIGM TO EMPOWER 21ST CENTURY LEARNERS: PARTICIPATORY ONLINE COURSE (POC) FOR HUBUNGAN ETNIK MODULE AT TAYLOR’S UNIVERSITY, MALAYSIA - Haniffa Beevi Abdul Jaleel; Wan Liyana Naznim Wan Omar Sukri; Enna Ayub (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The emergence of digital technologies in Education 4.0 has created a need in transforming face-to-face (F2F) learning into a fully virtual learning environment (VLE). As Massive Open Online Course (MOOC) booms up in Malaysian Education System in 2015, Hubungan Etnik (HE) course at Taylor’s University has been revolutionizing from traditional classroom learning to fully online course. This project, which was launched in 2016 was developed through an online social learning platform (Openlearning). Users experienced empowering interactive learning through targeted video contents and interactive assessments. The gamification elements such as progress tracking and online digital badges hold the students’ active participation throughout the course. However, the interactive content and motivation, not enough to promote the students’ self-regulation in VLE. The gaps that occur between F2F learning and VLE makes the students’ feel disconnected from a learning environment, contents and instructor. Therefore, the learning structure in this module has been shifted towards participatory assessments together integrating emotive factors which brings the students into deep learning via critical thinking and problem-solving skills. The purpose of this research is to investigate the level of students’ participation and achievement in the learning process. Through reflective writing on students’ learning experiences, qualitative data collected to analyze students’ active participation, acceptance, and achievement in HE module as a Participatory Online Course. The findings showed the emotive factors plays a huge role in promoting students’ deeper participation that leads to high motivation and engagement in learning as well close the gaps between F2F learning and VLE.